Determination of solubility of chlorides of d-elements in chloroaluminate melts - V. V. Karpov; V. A. Volkovich; I. B. Polovov; O. I. Rebrin (Chimica Techno Acta)
Solubility of several transition metal chlorides (NiCl2, CrCl2, MoCl3, FeCl2) was measured in KCl-AlCl3 based melts. It was found that the solubility of studied metal chlorides depends on K : Al mole ratio. MoCl3 solubility decreases with increasing AlCl3 content. Solubility of CrCl2 and FeCl2 reaches maximum at K : Al ratio of 1 and decreases when this ratio either de-creases or increases. The dependence of NiCl2 solubility on K : Al mole ratio is V-shaped with the maximum near 0.9-0.95. The effect of temperature on solubility of transition metal chlorides in KCl-AlCl3 melts was also investigated. Increasing temperature does not alter the character of «solubility – K : Al mole ratio» dependences.